Acceptability of Catfish Nugget in Toddler Integrated Health Service Post (Posyandu) of Dermo Subdistrict, Mojoroto District, Kediri City - Utami, Nuzul Dwi; Setyobudi, Sugeng Iwan (Journal of Global Research in Public Health, 2025)
A situational analysis was conducted in the working area of the Mrican Community Health Center, Kediri City, through surveys and SQ-FFQ interviews with mothers of toddlers. The data showed energy and protein intake deficits in toddlers. This study aims to develop catfish nuggets as a functional food for toddlers,  providing  an  alternative  nutritious  snack  for  those  who  are undernourished. The product was developed from local ingredients such as catfish, carrots, eggs, cornstarch, and white bread. Organoleptic test results showed the best acceptability of catfish nuggets. The average organoleptic value of a color parameter of catfish nuggets was 4.1, and chicken nuggets was 4.27. The aroma parameter of the catfish nugget was 4.27, and the chicken nugget was 3.63. The texture parameter of the catfish nugget was 4.2, and the chicken nugget was 3.13. The flavor parameter of the catfish nugget was 4.53, and the chicken nugget was 3.53. Catfish nuggets have more potential than chicken nuggets. The highest percentage of acceptance in color, aroma, texture, and taste parameters is  found in catfish nuggets. In color parameters, many say that catfish nuggets are lacking because the color is darker. The taste parameter is more savory in catfish nuggets.